Self-assemblied nanocomplexes based on biomimetic amphiphilic chitosan derivatives for protein delivery. (5th May 2015) - Wu, Minming; Dong, Hongwei; Guo, Kai; Zeng, Rong; Tu, Mei; Zhao, Jianhao
Highlights: Novel amphiphilic biomimetic chitosan derivative DCA–PCCs was synthesized. BSA and DCA–PCCs can self-assemble to form spherical nanocomplexes. BSA/DCA–PCCs nanocomplexes show excellent cytocompatibility and hemocompatibility. BSA/DCA–PCCs nanocomplexes exhibited a sustained drug release behavior. Abstract: A bio-inspired nanocarrier was developed for protein delivery based on biodegradable amphiphilic chitosan derivative (DCA–PCCs) with hydrophilic cell membrane mimic phosphorylcholine (PC) and hydrophobic deoxycholic acid (DCA) moieties, which was synthesized via the combination of Atherton–Todd reaction and carbodiimide coupling reaction. Using bovine serum albumin (BSA) as model protein, it was found that DCA–PCCs with suitable degree of substitution of PC and DCA moieties can load proteins by forming nanocomplexes via a solvent evaporation method. The physicochemical characteristics of BSA/DCA–PCCs nanocomplexes were investigated by Zetasizer, atomic force microscopy (AFM) and Fourier-transform infrared (FT-IR) spectroscopy. In vitro biological evaluation revealed BSA/DCA–PCCs nanocomplexes as blank DCA–PCCs nanoparticles had excellent cytocompatibility and hemocompatibility mainly due to the presence of cell membrane mimic phosphorylcholine. BSA release results suggested BSA/DCA–PCCs nanocomplexes showed a sustained release behavior following first order exponential decay kinetics. The results indicated DCA–PCCs provided a promising approach for effectively delivering therapeutic proteins.